A Commentary on de Sousa′s towards an Integrative Theory of Consciousness - Pereira Jr., Alfredo [UNESP] (Wolters Kluwer, 2013)
De Sousa′s comprehensive two-part review of a diversity of contemporary approaches to the study of consciousness is highly welcome. He makes us aware of a proliferation of theoretical and empirical approaches targeting a common theme, but diverging in many ways. He skilfully accomplishes a classification of kinds of approach, identification of the main representatives, their contributions, and respective limitations. However, he does not show how the desired integration could be accomplished. Besides summarising de Sousa′s efficient analytical work, I make critical comments and briefly report my contribution for the integration project.© MSM 2013.
Keywords: Astrocytes; Consciousness; Feeling; Integration; Neurons; Representation